Hate Speech in the Digital Age: Balancing Constitutional Freedoms with Just Regulation - Stanley, Connor (Maine Policy Review, 2025)
Each year the Margaret Chase Smith Library sponsors an essay contest for high school seniors. The essay prompt for 2025 asked students their opinion on the rights of speakers in the public square. Should people be allowed to express anything they desire no matter the ripple effect their words may cause? Or, should there be limitations on speech? If so, how far is too far? This is the first-place essay.